EVALUASI PENGELOLAAN OBAT BUFFER STOK DI UPTD INSTALASI FARMASI DINAS KESEHATAN KOTA PEMATANGSIANTAR TAHUN 2024 - Romauli Sihaloho; Arsiaty sumule, Ismi Noer Farida (CV. Adiba Aisha Amira, 2025)
Drug management including planning, storage and distribution is one of the most important tasks at the UPTD of the Pematangsiantar City Health Service pharmaceutical installation. Poor medication management will have a negative impact on the quality of service. The aim of this research is to evaluate the management of stock buffer drugs in 2023 installed at the Pematangsiantar health service pharmacy. The research was conducted in January-December 2023. This research was descriptive in nature with data obtained retrospectively. The data obtained was analyzed using indicators and compared with the research results. The results of the research show that the planning, storage and distribution at the UPTD pharmaceutical installation of the Pematang Siantar City Health Department does not fully meet the indicator standards. This is shown by 4 indicators that do not meet the standards, namely the percentage of accuracy in drug planning ; number and value of expired/damaged medicines ; drug storage system (not yet up to standard); and deviations in the amount of medicine distributed.